Development of a technology of vitaminized blended vegetable oils and their identification by the fatty acid and vitamin contents - Yevhenii Kotliar (Eastern-European Journal of Enterprise Technologies, 2018)
Due to the comparative analyses of physicochemical properties and fatty acid composition of vegetable oils, a reasonable choice has been made. Namely, sunflower, pumpkin, flaxseed, and camelina oils have been found optimal for the preparation of blends with a rational ratio of ω-6:ω-3 fatty acids in two-component (10:1, 5:1) and three-component (5:1) mixtures. A reasonable combination of vegetable oil blends with a rational ratio of ω-6:ω-3 fatty acids has been substantiated. Since oils belong to polyfunctional physiologically active products with a wide range of technological properties, they can be used with fat soluble vitamins (tocopherol and β-carotene). This reduces the oxidation processes in the vitaminized blended vegetable oils (VBVOs). A blended vegetable oil is a system in which PUFAs of the ω-6 and ω-3 groups are present in certain ratios and are subject to oxidative damage, to a greater extent due to the increased content of PUFAs. In accordance with the specifics of the blended oils as enriching ingredients, fat-soluble vitamins E (tocopherol) and β-carotene were used, which are not only physiologically important components for the human body but also active natural antioxidants. It has been found that adding a 0.2 % solution of β-carotene in the amount of 3.75 g and 1 % of tocopherol solution in the amount of 2.5 g provides 30 % of the daily requirement of these vitamins for the human body. The appropriateness of the joint use of tocopherol and β-carotene is based on the finding that it stabilizes oxidation and increases the induction period 1.5–2 times. The fatty acid composition of the created recipes of the blended systems with the ratio of PUFAs of the ω-6 and ω-3 families, in particular for healthy people’s nutrition with a ratio of ω-6:ω-3 being equal to 10:1; for adequate nutrition the ω-6:ω-3 ratio should be 5:1, which indicates the expediency of the selected vegetable oils for the creation of blended systems, balanced on the fatty acid composition exactly in the proposed ratios. The technologies of blending and vitaminizing vegetable oils have been developed and introduced at the Odesa Stone Fruit and Vegetable Oils Plant, AVA Ltd. (Ukraine). When solving the problems of substantiating the blending and vitaminization technologies, it has been proven that these operations can be performed with equipment that is present in almost all oil and fat processing factories. The proposed blending technology involves only two stages: stage 1 is the dosage of the prescription amount of oil 1 in a temperature-maintaining container; stage 2 is the dosage of the prescription amount of oil 2 in the container with oil 1 and mixing for 5.0...10 min at t=28…30 °С. It does not require much time and allows the preparation of oil and mixing within 10–15 minutes.